The importance of Intelligent Control Systems - Kavitha (International Journal of Human Computing Studies, 2019)
Intelligent control system combines the mathematical theory of control and artificial intelligence that is AI technology. In this paper, we will discuss in detail how the intelligent control system works and why it is used for. Also, we will cover its crucial importance in the field of technology along with its pros and cons. Artificial Intelligence is the need of the digital world to ease out work and copy the human brain. Intelligent control system take support of artificial intelligent to work for and why it is so important in the technological world. Its together with artificial intelligence called schemer which is to support such a paradigm. Schemer is worked to solve the difficult problem and work like a problem-solving agent which react, interact, and dynamically change the condition of difficult task situation to carry out problem-solving activities.